Obtenção de extratos voláteis e não voláteis de Pluchea sagittalis (Lam.) Cabrera (Quitoco) : processos e análises - Grandini, Camila Pereira (2017)
The growing concern of industries in finding natural inputs in place of synthetic ones in the production of bioactive products in the pharmaceutical, food and cosmetic areas motivated this research to the study of the biological activities of the volatile and non-volatile extracts of Pluchea sagittalis. This plant known as quitoco of spontaneous growth in nature is found in tropical regions having its origin in the South American continent. The goal of this study was to obtain volatile and nonvolatile extracts from the aerial parts of the quitoco and to evaluate the chemical composition and the biological activities of the extracts obtained. In order to obtain extracts from leaf and stem samples of P. sagittalis, without flowers and flower samples, two processes were used: Extraction by steam drag, to obtain volatile extracts, and supercritical extraction, to obtain non-volatile extracts. The chemical composition of the extracts obtained by steam drag was analyzed by gas chromatography coupled with mass spectrometer. The antimicrobial activity of leaf and stem essential oil was tested with the bacteria Staphylococcus aureus and Escherichia coli and also with the fungus Candida albicans, both tests were performed using the indirect bioautography technique where the oil showed growth inhibition for Staphylococcus aureus and for the fungus Candida albicans. Volatile extracts of leaves and stems and flowers obtained by steam extraction and supercritical fluid at 90 bar pressure were evaluated for their aromatic potential by means of sensorial (olfatometric) analysis, having as best evaluation the extract obtained by supercritical extraction of quitoco flowers.